Development of E-LKPD Based on Project Based Learning on Meeting Management Material for Office Management and Business Services Department - Restuningrum, Rizka Fajar (Journal of Vocational and Career Education, 2026)
This research is motivated by the fact that the Meeting Management course in the Office Management and Business Services (MPLB) at vocational high schools (SMK) tends to be theoretical, less interactive, and has minimal practical application. This results in low student engagement, limited creativity, and suboptimal meeting practice skills. Therefore, this study aims to develop a learning medium in the form of Project-Based Learning (PjBL)-based e-LKPD (Electronic Student Worksheet) to improve student engagement, skills, and understanding of meeting management.The research method used is Research and Development (R&D) with the ADDIE development model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The subjects were 36 12th-grade MPLB students at SMK Negeri 1 Wonosobo, two media experts, two material experts, and eight subject teachers. The research instruments included a validation sheet, a practicality questionnaire, and a pretest–posttest.The results showed that the PjBL-based e-LKPD developed was categorized as highly valid by the media and material experts. Practicality testing, based on teacher and student responses, demonstrated a practical category, as the media was easy to use, engaging, and supported project-based learning. Effectiveness testing demonstrated significant improvements in student learning outcomes, with differences in pretest and posttest scores, as well as increased student creativity and collaboration skills in planning and simulating meetings.Based on these results, it can be concluded that the Project-Based Learning-based E-LKPD product is suitable for use as an innovative learning medium that is interactive, contextual, and relevant to the needs of the workplace